Pengaruh Tagline Shopee “Gratis Ongkir” terhadap Minat Beli - Alvina Damaiyanti Mulyawan; Sisca Aulia (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
Technological innovation is growing rapidly in modern times, it cannot be denied that the trend of buying and selling online as a tool to meet needs. Shopee is an e-commerce platform that offers a variety of products. In an advertising campaign that is often used is the tagline, the tagline is used by companies for promotions to give an impression to consumers. Likewise with Shopee, Shopee offers free shipping which is then used as a tagline and included in various advertisements and events. The purpose of this study was to determine whether there was an effect of Shopee's